An Analysis of Translation Technique and Translation Quality in Poem Book Entitled Love & Misadventure - Aldita Prafitasari; MR Nababan; Riyadi Santosa (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This paper discusses a poetry translation, Love & Misadventure by Lang Leav into Indonesian translated by Aan Mansyur. The purpose of this study is to determine how the translator considers the translation techniques used to translate the poem into the target language and its impact of the translation quality in terms of accuracy and readability. Translation techniques are the means of delivery thought through the use of poetic language such as the repetition and rhyme of the poem. This research is descriptive-qualitative research which applies a purposive sampling technique. The data of this research are 30 poems. Two methods of data collection were applied; content analysis and Focus Group Discussion. The result of analysis provides two results. The first is the analysis show that the translation technique that dominantly used by the translator is Established Equivalence. There are 11 techniques which are applied in translating the selected poem, they are; established equivalent, modulation, amplification, variation, compensation, discursive creation, transposition, particularization, pure borrowing, literal, and reduction. The second is the translation quality of the translation. Most of the data of the poem belong to accurate and readable translation. It shows that there are 20 (67%) data of accurate translation, 10 (33%) data of less accurate translation, and there is no inaccurate translation. The research findings indicates that dealing with accuracy, established equivalence produce most accurate translation and dominantly used to translate the poem. It is due to the fact that Leav’s poem consist of simple style of language and choice of words. Meanwhile, discursive creation produces a less accurate translation. Dealing with readability, there are 27 data (90%) which are classified as readable translation, 2 data (7%) which are classified as less readable, and 1 datum (3%) is classified as unreadable translation from 30 data. All translation techniques used to translate the poem that is found in this research bring positive impact to the level of readability which means they are easy to be understood.